Geopolitical tensions fuel currency competition but US dollar and euro remain hard to displace - Sonali Chowdhry (DIW Weekly Report, 2025)
Geopolitical frictions and high levels of uncertainty in US policy are driving countries to reduce dependence on the US dollar and implement new policies to promote their own currencies for settling cross-border trade. This Weekly Report analyzes the reactions of firms to such measures, focusing on China's efforts to promote the renminbi globally. Leveraging detailed French customs data, the findings show that China's renminbi push spurred rapid growth in the currency's use in firm-level exports to China, driven by large and experienced exporters in consumer goods sectors. Crucially, renminbi adoption remained confined to China, displacing neither the US dollar nor the euro as the preferred invoicing currencies in other markets. These results highlight the limits to currency promotion efforts. Any transition to a multi-polar currency system is therefore likely to be gradual, with sharp disparities across firms and industries.
Keywords: F14; F23; F33; 330; International trade; Invoicing currency; Geoeconomics